Health education: A vital tool in changing environmental hygiene knowledge, attitudes and practices among food handlers in a tertiary care hospital of Delhi - Saurabh Chauhan; Mamta Parashar; Jyoti Khandekar; Mitasha Singh (Elsevier, 2024)
Background: Environmental hygiene in food establishments is an important determinant of health. Health education package using combination of strategies is essential in preventing cross-contamination. Objective: To determine change in environmental hygiene knowledge, attitudes and practices among food handlers following implementation of health education intervention. Methods: A before and after interventional study was conducted on 111 food handlers of food establishments in a tertiary care hospital of Delhi in 2021-22. Tool based on WHO & FSSAI guidelines was prepared with a scoring system to rate environmental hygiene knowledge (0-12), attitudes (0-10) and practices (0-12) including cleaning of surfaces, pest control, waste disposal & segregation, packaging of food along with utensil washing steps (0-10). Health education was given and scores on same tool were reassessed after 8 weeks of intervention. Nail bed swabs were taken as an indicator of bacteriological contamination. Results: The differences of mean scores of knowledge, attitudes and practices before & after intervention were statistically significant differences of 9.95 ± 0.95, 8.02 ± 0.68 and 7.91 ± 1.16 respectively (p < 0.05) while utensil washing practices before and after intervention were 2.78 ± 0.59 & 6.77 ± 0.74 with statistically significant difference of 3.99 ± 0.85. Before intervention, pathogenic organisms were isolated in nail bed swabs of 91 % of study participants while after intervention it was 12.6 %. Common species isolated were Klebsiella spp. (55.5 %), E. coli (15.9 %), Staphylococcus spp. (10.9 %) and Acinetobacter spp. (9.9). Conclusion: Improvement in environmental hygiene KAP emphasizes need of ensuring implementation of existing guidelines. Thus, health education using planned combination of channels and strategies can achieve desired change.